2010
DOI: 10.4292/wjgpt.v1.i6.135
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal pseudo-obstruction in inactive systemic lupus erythematosus: An unusual finding

Abstract: Chronic intestinal pseudo-obstruction (CIP) is an infrequent complication of an active systemic lupus erythematosus (SLE). We illustrate a case of SLE inactive-related CIP. A 51-year old female with inactive SLE (ECLAM score 2) was hospitalized with postprandial fullness, vomiting, abdominal bloating and abdominal pain. She had had no bowel movements for five days. Plain abdominal X-ray revealed multiple fluid levels and dilated small and large bowel loops with air-fluid levels. Intestinal contrast radiology d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…This result is consistent with previous reports showing that IPO and ureterohydronephrosis can occur with low systemic disease activity even in a stable state of other organ involvement. 22 Moreover, in our study, the SLEDAI scores indicated high disease activity in only 29.5% of the patients, but 50.8% of the patients needed a 3-day pulse of methylprednisolone therapy, suggesting that in SLE patients with IPO and/or ureterohydronephrosis the SLEDAI score is not a reliable reference for evaluating the disease activity and deciding the initial dose of steroids. It has to be emphasized that the SLE patients with IPO and/or ureterohydronephrosis should all be regarded as having active SLE independent of the scoring and given early aggressive treatment.…”
Section: Discussioncontrasting
confidence: 64%
“…This result is consistent with previous reports showing that IPO and ureterohydronephrosis can occur with low systemic disease activity even in a stable state of other organ involvement. 22 Moreover, in our study, the SLEDAI scores indicated high disease activity in only 29.5% of the patients, but 50.8% of the patients needed a 3-day pulse of methylprednisolone therapy, suggesting that in SLE patients with IPO and/or ureterohydronephrosis the SLEDAI score is not a reliable reference for evaluating the disease activity and deciding the initial dose of steroids. It has to be emphasized that the SLE patients with IPO and/or ureterohydronephrosis should all be regarded as having active SLE independent of the scoring and given early aggressive treatment.…”
Section: Discussioncontrasting
confidence: 64%
“…We summarize available clinical and immunological characteristics of CTD associated with CIPO and treated with octreotide in Table 1 [316]. Of 24 CTD patients with CIPO, there were 20 (83%) with SSc or SSc/PM overlap syndrome, and of the remaining 4 two had SLE, one PM, and one DM (the latter, our case reported here).…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 30 cases of CIPO secondary to SLE have been reported so far, with the largest case series from Hong Kong. 5,8,9 It usually occurs in active SLE, although it could manifest during inactive SLE. 8 Mok et al reported that five out of six patients had CIPO as the first manifestation of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,9 It usually occurs in active SLE, although it could manifest during inactive SLE. 8 Mok et al reported that five out of six patients had CIPO as the first manifestation of SLE. 5 In addition to CIPO, these patients also had concomitant glomerulonephritis (38.8%), thrombocytopaenia (27.8%) and autoimmune haemolytic anaemia (11.1%).…”
Section: Discussionmentioning
confidence: 99%